2019
DOI: 10.1017/s0269964819000408
|View full text |Cite
|
Sign up to set email alerts
|

Ordering Results on Extremes of Exponentiated Location-Scale Models

Abstract: In this paper, we consider exponentiated location-scale model and obtain several ordering results between extreme order statistics in various senses. Under majorization type partial order-based conditions, the comparisons are established according to the usual stochastic order, hazard rate order and reversed hazard rate order. Multiple-outlier models are considered. When the number of components are equal, the results are obtained based on the ageing faster order in terms of the hazard rate and likelihood rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The following example provides a demonstration of Theorem 3.5. , π‘₯ > 0, be the generator of the Gumbel-Barnett survival copula. Set the three-dimensional vectors 𝝀 = 𝝁 = (0.6, 1.1, 2), 𝜽 = (𝑒 5 , 𝑒 7 , 𝑒 9 ), 𝜹 = (𝑒 6 , 𝑒 8 , 𝑒 10 ), 𝒑 = (0.11, 0.21, 0.31) and 𝒑 * = (0.62, 0.70, 0.82). Furthermore, we can check that πœ“ satisfies Conditions (ii) and (iii) in Theorem 3.5.…”
Section: Remark 34 (I) For the Independence Survival Copula With Gene...mentioning
confidence: 99%
See 2 more Smart Citations
“…The following example provides a demonstration of Theorem 3.5. , π‘₯ > 0, be the generator of the Gumbel-Barnett survival copula. Set the three-dimensional vectors 𝝀 = 𝝁 = (0.6, 1.1, 2), 𝜽 = (𝑒 5 , 𝑒 7 , 𝑒 9 ), 𝜹 = (𝑒 6 , 𝑒 8 , 𝑒 10 ), 𝒑 = (0.11, 0.21, 0.31) and 𝒑 * = (0.62, 0.70, 0.82). Furthermore, we can check that πœ“ satisfies Conditions (ii) and (iii) in Theorem 3.5.…”
Section: Remark 34 (I) For the Independence Survival Copula With Gene...mentioning
confidence: 99%
“…The general exponentiated location-scale model serves this purpose very well due to its great flexibility. Das et al [9], Das and Kayal [7] and Das et al [8] considered (1.1) to obtain different stochastic ordering results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, stochastic comparisons of the largest claim amounts when random claims have ELS models have not been addressed in the literature so far. However, some generalized models to study ordering properties of extreme order statistics in the context of reliability studies can be found in [7][8][9][10][11]16]. In this paper, we address this problem and derive sufficient conditions for the stochastic comparison of the largest claim amounts in the sense of various stochastic orderings.…”
Section: Introductionmentioning
confidence: 99%